Genetic susceptibility to autoimmune liver disease - Mattner, Jochen (Baishideng Publishing Group Co., Limited, 2011)
Autoimmune hepatitis (AIH), primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC) are considered as putative autoimmune diseases of the liver. Whereas strong evidence that bacterial infection may trigger PBC exists, the etiologies for PSC and AIH remain unknown. Although there have been significant discoveries of genetic polymorphisms that may underlie the susceptibility to these liver diseases, their associations with environmental triggers and the subsequent implications have been difficult to elucidate. While single nucleotide polymorphisms within the negative costimulatory molecule cytotoxic T lymphocyte antigen 4 (CTLA-4) have been suggested as genetic susceptibility factors for all three disorders, we discuss the implications of CTLA-4 susceptibility alleles mainly in the context of PBC, where Novosphingobium aromaticivorans, an ubiquitous alphaproteobacterium, has recently been specifically associated with the pathogenesis of this devastating liver disease. Ultimately, the discovery of infectious triggers of PBC may expand the concept of genetic susceptibility in immune-mediated liver diseases from the concept of aberrant immune responses against self-antigens to insufficient and/or inappropriate immunological defense mechanisms allowing microbes to cross natural barriers, establish infection and damage respective target organs.